Unraveling the effects of wet and dry areas on carbon emissions in an intermittent Mediterranean stream - Alba Camacho‐Santamans; Biel Obrador; Camille Minaudo; Lídia Cañas; Yao Wang; Fernanda Mejía‐Peralta; João M. M. Bega; Jorge J. Montes‐Pérez; Daniel von Schiller (Limnology and Oceanography, 2026)
Stream hydrological regimes are increasingly altered by water extraction, land‐use change, and climate change, leading to prolonged streambed desiccation in many regions. These alterations significantly impact biogeochemical processes within stream networks. To date, most research on the carbon (C) cycle in aquatic systems has focused on inundated areas, thereby neglecting the potential role of dry streambeds in biogeochemical dynamics. However, some studies have shown that dry streambeds substantially influence C fluxes within fluvial environments, although with limited temporal replication. In this study, we quantify the contribution of dry areas to gaseous C exchange in an intermittent Mediterranean stream. Over 2 yr, we monitored the spatial extent of wet (i.e., inundated) and dry (i.e., air‐exposed) areas and measured carbon dioxide (CO 2 ) and methane (CH 4 ) fluxes along a 100‐m reach using high‐frequency automatic sensors and in‐situ sampling every 2–3 weeks. We found that areal C fluxes were higher in wet compared to dry areas. Fluxes in wet areas displayed strong temporal dynamics, with peaks during phases of rewetting and contraction of the stream. In contrast, fluxes in dry areas were relative stable over time and accounted for 46% of the total reach‐scale C exchange with the atmosphere during the study period. These results emphasize the importance of accounting for inundated and intermittently dry areas when analyzing C exchange dynamics in intermittent streams. This issue is particularly relevant in the current context of climate change, with climate‐driven hydrological changes in many of the world's regions.